Flutuação populacional e controle químico de Ochetina uniformis (Pascoe, 1881) (Coleoptera, Erirhinidae, Erirhininae) em área de arroz irrigado - Possebon, Sandro Borba (2007)
A field population survey of Ochetina uniformis (Pascoe, 1881) (Coleoptera: Erirhinidae, Erirhininae) was performed at Santa Maria, RS, in a flooded rice commercial field, between quarterly June 2005 to July 2006 (rice was grown between October 2005 to March 2006). A stratified sampling was used approach; quarterly 90 randomized samples were taken in plots measuring 0.25 x 0.25 m, with total of 24 samples during the survey period. There was a reduction in the population of O. uniformis starting from July 2005 to January 2006. Soil tillage affected the population of O. uniformis in the rice field, and did not affected the population on the hibernation areas. Some areas showed no insects and another showed a few number of individuals, indicting grouping behavior. Adults of O. uniformis, are concentrated in the levees, representing 44% of the total number os insects. The population reduced between the levees to the middle of the field, with averaging 14% inside the field. From January to February, a reduced number of adults were verified in the levee. Outside the cultivated area there were no adults of O. uniformis during the 12 months survey period. In this study high populations of O. uniformis, were concentrated in the levees of the field for a period of six months, from July to December of 2005. It was observed a large number of dead adult of O. uniformis infected by Beauveria bassiana.